The use of hedging devices in Malaysian doctoral candidature defense sessions / Alexander C. Damiano-Nittoli - Alexander C., Damiano-Nittoli (2016)
The use of hedging in Malaysian spoken academic discourse works to mitigate the force of the argument made by the speaker in that context. Hedging can be generally focused on mitigating the specific content of the argument or the more interpersonal nature of communication in various contexts. The goal of the present research was to understand hedging specifically in the genre of doctorate oral defense in the Malaysian context. The study began by addressing the numerical incidence of hedging in Malaysian defense by comparing the incidence of hedging in the Malaysian context with data taken from oral defenses in the American context. Taking the frequency of hedging forms and functions in both contexts provides a foundation for understanding the nature of hedging use in Malaysian doctorate defense and also gives a platform for the rest of the study. The next portion of the present research took the observations seen about hedging in the Malaysian context and put them in terms of the culture surrounding the defense. Culture is a broad term and when it is applied to second language users of English, as in the Malaysian defense, it is generally boiled down to national linguistic culture. This goal of this study, however, was to look more holistically, and at a greater depth, regarding the various levels of culture that may influence and shape the numerical and qualitative observations made about hedging in Malaysian academic discourse. The study found that national culture and the dynamic between L1/L2 influenced the variety of hedges chosen in Malaysian PhD oral defense. It was also found that power distance in the educational culture surrounding the defense had an effect on the interpersonal hedging used by Malaysian speakers and also the gap in hedging use between panel members and candidates. The last finding of the study was that disciplinary culture was observed to influence hedging specifically in referencing other work and testing theory to build an argument.